(untitled) (ModaPalavra e-periódico, 2026)
Clothing, in addition to expressing aesthetic and cultural aspects, also influences issues related to physical and emotional health. However, the role of clothing as a form of self-care is rarely considered, creating a gap between fashion and health. This article aims to understand how healthcare professionals perceive fashion and clothing in the context of healthcare, considering symbolic, functional, and environmental dimensions. This knowledge is relevant to understanding how healthcare practice can contribute to the creation of products and strategies aimed at health promotion. The qualitative research used semi-structured interviews with eleven professionals from different healthcare fields, whose accounts were analyzed using content analysis. Five categories emerged: functionality and comfort; hygiene, safety, and prevention; identity and self-esteem; motivation and therapeutic goals; and environmental perception of clothing. The results indicate that clothing influences perceptions of comfort, identity, and well-being, as well as acting as support in rehabilitation processes, self-esteem, and autonomy. In some cases, interviewees reported using clothing as a tool for therapeutic mediation or to stimulate self-care. On the other hand, a lack of awareness was observed regarding the environmental impacts of clothing production and disposal, indicating the need to broaden the dialogue between fashion, health, and sustainability. It is concluded that clothing should be recognized as an active element in care practices, reinforcing the dialogue between fashion and health and contributing to the training of professionals, encouraging the creation of products more sensitive to human needs.